2017
DOI: 10.1021/acs.energyfuels.7b00313
|View full text |Cite
|
Sign up to set email alerts
|

Vaporization of Crude Oil by Supercritical CO2 at Different Temperatures and Pressures: Example from Gorm Field in the Danish North Sea

Abstract: The effect of temperature on supercritical carbon dioxide (SC-CO 2 ) extraction of crude oil from the Gorm oil field of the North Sea was investigated at temperatures of 40−70 °C and pressures of 20−60 MPa. MALDI-TOF, GC-MS, and NMR analyses were conducted in order to characterize the oil. Generally, the total recovery and vapor recovery increased, while the liquid recovery decreased, when the temperature was increased from 40 to 70 °C. At lower temperatures (40 and 50 °C), the liquid recovery increased from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The reduction of the interfacial tension is more significant at high pressures [22, 23]. At high pressures, CO 2 can vaporize the light and intermediate components of the oil, which is considered as one of the oil recovery mechanisms, especially at high pressure reservoirs [24]. Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of the interfacial tension is more significant at high pressures [22, 23]. At high pressures, CO 2 can vaporize the light and intermediate components of the oil, which is considered as one of the oil recovery mechanisms, especially at high pressure reservoirs [24]. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Rudyk et al. [24] investigated the oil recovery by vaporization mechanism using supercritical CO 2 at various conditions of temperatures and pressures. Their results showed that crude oil vaporization by supercritical CO 2 can result in favorable recovery factors at high pressure reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with conventional CO 2 -EOR, the soaking stage after CO 2 fracturing makes it possible for supercritical CO 2 to give full play to its miscibility and extraction effect on crude oil under high pressure, thereby enhancing oil recovery and CO 2 sequestration of tight oil reservoirs. ,, To explore the interaction mechanism of supercritical CO 2 and crude oil under high-pressure conditions, the lab experiments described below were carried out.…”
Section: Resultsmentioning
confidence: 99%
“…During fracturing, CO 2 undergoes complex phase changes under the influence of external temperature and pressure changes, which will change the physical properties of CO 2 and affect the stimulation and CO 2 sequestration effect. 21,22 Therefore, the investigation of CO 2 phase evolution in the fracturing process forms the first step in studying the stimulation and CO 2 sequestration mechanisms. Accordingly, a pilot field test of fracturing was carried out in the H 87 tight oil block of the Jilin Oilfield, and sensors were set at the bottom of the well to collect bottom-hole temperature and pressure data during and after fracturing.…”
Section: Methodsmentioning
confidence: 99%
“…More effective enhanced oil recovery (EOR) methods that ensure an economical production of the tail end (trapped oil) from these oil fields are being continuously researched. Such technologies include thermal flooding (steam injection, in-situ combustion), chemical (surfactants, polymers, solvents, alkali) flooding, miscible and immiscible gas displacement, and microbial EOR to produce the hard-to-recover oils in older fields [32][33][34]. Among these techniques, chemicals flooding techniques have emerged as one of the most effective techniques to improve crude oil recovery from maturing fields.…”
Section: Application Of Surfactants To Enhance Oil Recoverymentioning
confidence: 99%